2020
DOI: 10.1007/s40590-020-00287-y
|View full text |Cite
|
Sign up to set email alerts
|

The biplanar tree graph

Abstract: The complete twisted graph of order n, denoted by T n , is a complete simple topological graph with vertices u 1 ; u 2 ;. . .; u n such that two edges u i u j and u i 0 u j 0 cross if and only if i\i 0 \j 0 \j or i 0 \i\j\j 0. The convex geometric complete graph of order n, denoted by G n , is a convex geometric graph with vertices v 1 ; v 2 ;. . .; v n placed counterclockwise, in which every pair of vertices is adjacent. A biplanar tree of order n is a labeled tree with vertex set fv 1 ; v 2 ;. . .; v n g hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Originally introduced by Harborth and Mengersen in 1992 [ 21 ], twisted drawings have been thoroughly investigated; see for example [ 4 , 9 , 13 , 24 , 27 , 28 , 34 ]. Pach, Solymosi, and Tóth [ 28 ] showed that every simple drawing of contains an induced subdrawing of a complete graph on vertices which is either convex 3 or twisted .…”
Section: Introductionmentioning
confidence: 99%
“…Originally introduced by Harborth and Mengersen in 1992 [ 21 ], twisted drawings have been thoroughly investigated; see for example [ 4 , 9 , 13 , 24 , 27 , 28 , 34 ]. Pach, Solymosi, and Tóth [ 28 ] showed that every simple drawing of contains an induced subdrawing of a complete graph on vertices which is either convex 3 or twisted .…”
Section: Introductionmentioning
confidence: 99%